Experimental Investigation on Energy Dissipation in Diversion Tunnel at the Head of Canal - ZHONG Kun, YAN Fu-gen, GUO Jian-hua, YI Shun, LI Min-kang (长江科学院院报)
[Objective] The flow patterns of energy dissipation inside tunnels are complex, and theoretical calculations cannot meet design requirements. This research aims to: (1) verify the rationality of design parameters for energy dissipation in diversion tunnels at canal head based on hydraulic model tests; (2) propose an energy dissipation layout suitable for specific projects through model optimization to address high wave height inside the tunnel, insufficient clearance below the tunnel crown, and cavitation and erosion. [Methods] A hydraulic model test with a scale of 1∶1.5 was selected to simulate the diversion channel, pressurized tunnel, in-tunnel gate chamber, energy dissipation section, and a downstream section of free-flow tunnel. Additionally, an emergency gate shaft and the ventilation pipe behind the gate were simulated. A water tank was used as the model reservoir. The project involved three different discharge conditions, each with varying reservoir water levels, resulting in eight typical working conditions for testing. Then, based on the hydraulic model test results under different conditions, the downstream flow pressure characteristics, cavitation characteristics of the weir surface behind the operating gate, pressure characteristics of the gradually expanding stilling basin floor and sidewalls, flow connection patterns, and energy dissipation performance were obtained. Finally, the dimensions of the stilling basin section and the free-flow tunnel were improved, and wave suppression measures were optimized based on the test results. [Results] The hydraulic model test revealed shortcomings in the original energy dissipation scheme and proposed a combined layout of “stilling basin + wave suppression beam” suitable for in-tunnel energy dissipation. The test results showed: 1) the maximum wave height inside the free-flow tunnel was reduced by 67%, and the tunnel crown clearance met safe water conveyance requirements; 2) The local minimum cavitation number of the water flow at the curved section of the weir surface and the expanded section of the sidewalls behind the operating gate was about 0.37, indicating a low likelihood of cavitation erosion; 3) The root mean square of fluctuating pressure at measuring points along the stilling basin floor did not exceed 1.0×9.81 kPa, meeting structural design requirements. [Conclusion] This study proposes a combined energy dissipation method of “stilling basin + wave suppression beam” to address problems of high wave height and insufficient tunnel crown clearance in the original scheme. Compared with traditional submerged energy dissipators, the combined method significantly improves dissipation efficiency and has better energy dissipation characteristics. Hydraulic model tests verify the feasibility of the optimized scheme. The energy dissipation scheme is effective in solving the problems of large waves and insufficient tunnel crown clearance in similar projects. It is effective under multiple reservoir water levels and discharge conditions, and the wave suppression beam, as an in-tunnel energy dissipation structure, has little impact on tunnel flow capacity, demonstrating certain universality.